Exploring Teachers' Strategies and Challenges in Enhancing Vocabulary Skills of Elementary School Students - Hernita Ratna Aulia (Raja Zulkarnain Education Foundation, 2026)
This study aims to explore: 1) vocabulary teaching strategies used by English teachers in elementary schools; 2) the implementation of vocabulary teaching strategies in classroom practices and activities; 3) the challenges faced by teachers in improving students' vocabulary skills. This study used a descriptive qualitative design with data collection through a questionnaire consisting of closed-ended and open-ended questions administered to six elementary school teachers. The participants of this study were six elementary school English teachers. They were selected using a purposive sampling technique, based on their experience in teaching English at the elementary school level. The selection of participants was intended to obtain relevant and context-specific insights into vocabulary teaching practices in elementary school classrooms. Data were analyzed using thematic analysis to identify key patterns related to teachers' teaching practices, challenges, and solutions. The results of the study: 1) teachers tend to use interactive and visual-based strategies, namely flashcards, pictures, videos, and game-based activities to support vocabulary learning; 2) in teaching practices, vocabulary is introduced through visual representations and reinforced through repetition and practice; 3) teachers face several challenges, particularly limited exposure to English outside the classroom and constraints on students' learning motivation and attention. To address student motivational challenges, teachers employ various adaptive strategies, including creating a fun learning environment and employing a variety of methods. This research illustrates real-world classroom practices and emphasizes the importance of teacher creativity in vocabulary learning. Future research should involve more participants to obtain more comprehensive findings.